Production of triterpenoid compounds from Ganoderma lucidum spore powder using ultrasound-assisted extraction. Issue 3 (15th March 2020) - Shen, Shuang-Fei; Zhu, Li-Fang; Wu, Zijing; Wang, Guangkun; Ahmad, Zeeshan; Chang, Ming-Wei
Abstract: When ingested as a dietary supplement, Ganoderma lucidum spore powders (GLSP) provide various health benefits such as enhanced immunity, liver protection and anti-cancer effects. In this study, triterpenoid extraction from GLSP was achieved using an ultrasound-assisted process which was optimized using response surface methodology (RSM). Ultrasound-assisted extraction (UAE) was also compared to the most conventional chemical extraction method. For UAE, optimum extraction conditions were found to be ethanol concentration = 95% v/v; solvent to solid ratio = 50:1 mL/g; ultrasound time = 5.4 min; ultrasound power = 564.7 w, and ultrasound probe distance = 8.2 cm. At optimal UAE conditions, no significant differences were found between experimental (0.97 ± 0.04 %) and predicted values (99%); which indicates appreciable correlation at the 97% confidence interval. The findings show the application of Box–Behnken design (BBD) to predict and optimize triterpenoid yield for UAE of triterpenoid from GLSP. Furthermore, glucose consumption was 2.68 times that of control samples when tested with insulin-resistant HepG2 cell, showing potential use in type 2 diabetes. In addition, triterpenoid extracts show good biocompatibility and inhibition of antioxidant activity.